Repeat Stereotactic Radiosurgery for Progressive or Recurrent Vestibular Schwannomas. Issue 4 (October 2019) - Iorio‐Morin, Christian; Liscak, Roman; Vladyka, Vilibald; Kano, Hideyuki; Jacobs, Rachel C; Lunsford, Dade L; Cohen‐Inbar, Or; Sheehan, Jason; Emad, Reem; Karim, Khalid Abdel; El‐Shehaby, Amr; Reda, Wael A; et al.
Abstract : BACKGROUND : Stereotactic radiosurgery (SRS) is a highly effective management approach for patients with vestibular schwannomas (VS), with 10‐yr control rates up 98%. When it fails, however, few data are available to guide management. OBJECTIVE : To perform a retrospective analysis of patients who underwent 2 SRS procedures on the same VS to assess the safety and efficacy of this practice. METHODS : This study was opened to centers of the International Gamma Knife Research Foundation (IGKRF). Data collected included patient characteristics, clinical symptoms at the time of SRS, radiosurgery dosimetric data, imaging response, clinical evolution, and survival. Actuarial analyses of tumor responses were performed. RESULTS : Seventy‐six patients from 8 IGKRF centers were identified. Median follow‐up from the second SRS was 51.7 mo. Progression after the first SRS occurred at a median of 43 mo. Repeat SRS was performed using a median dose of 12 Gy. Actuarial tumor control rates at 2, 5, and 10 yr following the second SRS were 98.6%, 92.2%, and 92.2%, respectively. Useful hearing was present in 30%, 8%, and 5% of patients at first SRS, second SRS, and last follow‐up, respectively. Seventy‐five percent of patients reported stable or improved symptoms following the second SRS. Worsening of facial nerve function attributable to SRS occurred in 7% of cases. There were no reports of radionecrosis, radiation‐associated edema requiring corticosteroids, radiation‐related neoplasia, or death attributable to the repeat SRS procedure. CONCLUSION : Patients with progressing VS after radiosurgery can be safely and effectively managed using a second SRS procedure.